EKSPLORASI SENI DALAM MENGASAH PEMIKIRAN KRITIS DI POJOK BACA PARUDONGKA - Wardani, Abellia Anggi (UI Scholars Hub, 2025)
The transmigration program in Parudongka Village, which began in 2016, has brought forth a young generation facing limited infrastructure, including restricted access to learning resources. This condition underlies the establishment of Pojok Baca Parudongka as an art-based literacy space. The purpose of this study is to encourage critical thinking, foster the courage to ask questions, and enhance reading interest through interactive literacy activities. The research employs Freire’s (1968) cultural action theory framework, which emphasizes dialogue, praxis, and critical consciousness as means to achieve educational liberation. In addition, it adopts Conde’s (2021) art-based approach focusing on narrative inquiry, visual storytelling, and art journaling. The activities target elementary and junior high school participants in the Parudongka transmigration area, conducted from August to November 2025. The results indicate that Pojok Baca effectively enriches literacy experiences, stimulates curiosity, and facilitates critical dialogue between participants and researchers. Ultimately, Pojok Baca Parudongka serves as an art-based community literacy space that functions as a strategic medium to strengthen the reading culture and develop the critical thinking capacity of young people in the transmigration area.